Association between triglyceride-glucose index and the risk of stroke among moyamoya patients: a single-center retrospective study - Zhang, Chi; Guo, Kai; Xu, Hong; Kong, Gang; Liu, Chuanghong (Frontiers in Neurology, 2025)
BackgroundMoyamoya disease increases the risk of strokes by impairing cerebral circulation, significantly affecting patients’ quality of life. Despite the profound implications of this condition, there is a limited body of research exploring the factors that contribute to strokes in patients with Moyamoya disease. This study aims to evaluate the predictive value of the triglyceride-glucose index (TyG index) in forecasting stroke events among individuals diagnosed with moyamoya disease.MethodsA total of 84 patients diagnosed with Moyamoya disease were treated at Changshu First People’s Hospital from 01 January 2019 to 31 October 2024 were included in this study. We systematically collected and analyzed their clinical histories, laboratory test results, and baseline data. The patients were classified into two groups based on their history of cerebral stroke. Subsequently, we conducted a comparison and analysis of the TyG index between these two groups.ResultsThe TyG index observed in patients with moyamoya disease who have a history of cerebral stroke was significantly elevated compared to that of patients without such a history. This difference was found to be statistically significant (p < 0.05). Furthermore, regression cubic splines analysis indicated a noteworthy linear relationship between the TyG index and the occurrence of cerebral stroke events.ConclusionIn individuals diagnosed with Moyamoya disease, the TyG index has been shown to have a significant correlation with the risk of cerebral stroke. Furthermore, it has the potential to serve as an effective predictor for the occurrence of stroke.